REDEFINING ARABIC TEACHER COMPETENCIES FOR DIGITAL LEARNING: A CONCEPTUAL REVIEW BASED ON TPACK AND DIGCOMPEDU - Muhammad Ediyani; Warul Walidin AK; Saifuddin Dhuhri (Academic Bright Collaboration, 2025)
This study aims to redefine Arabic teacher competencies for digital learning in the context of educational transformation. Rapid developments in digital technology, artificial intelligence, and online learning environments have significantly changed the paradigm of language education, requiring Arabic teachers to possess competencies beyond traditional linguistic mastery and conventional pedagogy. This study employed a qualitative conceptual review using a library research approach. Literature was collected from Scopus-indexed journals, educational policy documents, books, and international competency frameworks, including TPACK and DigCompEdu. Sources were identified through systematic searches in Google Scholar, Scopus, and ERIC using keywords related to Arabic language education, teacher competence, digital pedagogy, and educational transformation. The selected literature was analyzed through thematic coding and conceptual synthesis. The review identified six major dimensions of Arabic teacher competence in the digital era: (1) digital pedagogical competence, (2) technological integration competence, (3) digital literacy competence, (4) collaborative and communication competence, (5) adaptive and innovative competence, and (6) ethical and humanistic competence. These dimensions collectively support effective technology-enhanced Arabic language learning while maintaining pedagogical quality and ethical responsibility. The study is limited to conceptual analysis and does not include empirical validation. Future research is recommended to test and refine the proposed competency framework through field-based studies involving Arabic language teachers and educational institutions. This study offers an integrated conceptual framework for Arabic teacher competencies by synthesizing TPACK, DigCompEdu, constructivist learning theory, communicative language teaching, and 21st-century skills. The framework contributes to the development of Arabic teacher education, professional standards, and policy initiatives for digital learning.